Phytoremedial Potential of a New Chemotype of Ocimum kilimandscharicum Guerke from Kumaun Himalaya. Issue 3 (4th May 2018) - Kunwar, Gitu; Pande, Chitra; Tewari, Geeta; Bhatt, Sunita; Tripathi, Sonal
Abstract: Plant productivity and safety of agricultural crops growing in metal contaminated soils is emerging as a major environmental problem affecting human health. To assess the effect of metals on herbage and oil productivity and the feasibility of growing aromatic crops in metal contaminated areas, a green house pot experiment was designed in which saplings of Ocimum kilimandscharicum were planted in copper, lead and cadmium amended soils. The aerial parts of the plants were harvested after 120 days and were subjected to hydrodistillation using Clevenger. The oil composition was analyzed by GC and GC-MS. Metal content in soil and plant was determined by AAS. Significant variations were observed in the fresh weight and plant productivity while the composition of essential oil did not exhibit marked variation as compared to the control. Despite the presence of copper, lead and cadmium in the plants, they showed vigorous growth with no symptoms of morpho-phytotoxicity.